Multivariate Analysis for Morphological Characteristics of N’Dama Cattle Breed in Two Agro-ecological Zones of Côte d’Ivoire - Edouard, N’goran Kouame; Lacine, Bamba Kalo; Cyrille, Kouassi N’Gouan; Etienne, Loukou N’Goran; Guiguigbaza-Kossigan, Dayo; Mamadou, Sangare; Valentine, Yapi-Gnaore Chia (European Scientific Journal, ESJ, 2018)
Information on morphological characteristics is a prerequisite to sustainable breed improvement, utilization, and conservation. In this study, 108 N’Dama cattle cows from 11 farms of central and northwestern regions of Côte d’Ivoire were described using visual appreciation criteria and linear body measurements. The variables were studied using principal component analysis (PCA) and discriminant analysis. Results indicated that the most common N’Dama is fauve (83.33%) and it has straight back profile (69.44%) and lyre horn (74.07%). Agroecological zone has a significant (p˂0.01) effect on linear body measurements of N’Dama. The central region animals had higher head width (18.94 ± 2.18 cm), skull length (22.51 ± 2.18 cm), skull width (16.51 ± 1.72 cm), muzzle circumference (40.83 ± 2.58 cm), distance between horns (15 ± 1.90 cm), ear length (17.46 ± 2.57 cm), chest length (160.11 ± 15.8 cm), chest depth (71.55 ± 7.41 cm), and body length (125.13 ± 12.22cm) than those of northwestern region N’Dama. Thus, their respective values were: 15.41 ± 2.85 cm, 18.62 ± 2.6 cm, 12.44 ± 3.94 cm, 38.8 ± 2.61 cm, 13.72 ± 1.52 cm, 16.41 ± 1.61 cm, 143.84 ± 8.35 cm, 65.25 ± 4.1 cm, and 119.18 ± 12.38 cm. PCA revealed that N’Dama morphometric variability performed from the 9 variables (Lt, lt, Lc, lc, pt, hg, Pth, Lcp and Lf) were more associated with the first two factors. In regards to the discriminant analysis, these 9 variables distinguished the N’Dama significantly (p˂0.05) into two populations that corresponds with the two agroecological zones.